DEVELOPMENT OF MESOSCALE NUMERICAL MODEL FOR PREDICTING DAMAGE DUE TO LOW-VELOCITY IMPACT ON UNIDIRECTIONAL COMPOSITE LAMINATES - Mahardika, Kafi
Composite materials have been widely used especially in transportation industries due to their lightweight properties which makes them more cost-effective. The use of composite for external possesses risks since it may be subjected to low-velocity impacts such as splash of rocks during in-service and dropping of tools and debris during maintenance where it will affect composite performance. Therefore, it is important to understand the effect of this impact on the composite. The analysis will be done by using numerical method and consequently, a model of the composite must be developed. The modeling strategy that was implemented in this work in developing mesoscale numerical model of a thermoplastic composite is to model each ply into two regions, namely resin-rich region, and fiber-rich region. To predict the delamination phenomenon that might occur for composites under low-velocity impact case, a cohesive element is embedded in between dissimilar ply orientation. The proposed finite element model does not correlate strongly with the experiment result both from the force-displacement graph and delamination area. Furthermore, parametric study is conducted to investigate the influence of various parameters on the global response of the modeling results. The finite element model is expected to serve as an initial reference for future research in similar developments.